Pelatihan Pembuatan Sosis dan Bakso yang Mengandung Bagan Antioksidan Alami sebagai Pangan Fungsional pada Masyarakat Desa Sembung, Lombok Barat - Yulianto, Wahid; Kisworo, Djoko; Bulkaini, Bulkaini; Dewi Wulandani, Baiq Rani; Haryanto, Haryanto; Fahrullah, Fahrullah (Universitas Mataram, 2024)
Sembung Village produces chilli that can be used as a source of antioxidant ingredients in functional processed meat products. The activity was carried out through two methods: Demonstration and Participation. The training started with an explanation of processed meat products, including tools and materials, principles of manufacturing methods, packaging, and presentation. The text explains the meaning of antioxidants, how they prevent oxidation, and which natural ingredients contain them. Afterwards, participants were given the opportunity to practice making sausages and meatballs through demonstrations. The majority of attendees were PKK cadres from each hamlet in Sembung Village. The training provides additional information on how to produce meatballs and sausages with added value in the form of healthy, natural antioxidant ingredients. Some participants have experience in meat processing. It can be concluded that the training activity has equipped the Sembung Village community with knowledge and skills that can be utilised to improve their welfare..